Gambaran Penyimpanan obat di gudang farmasi RSUD Bolaang Mongondow Selatan - Alfamega Pinasang; Gayatri Citraningtyas; Imam Jayanto; Mahendra Kusuma Nugraha (PHARMACON, 2023)
The storage of medicines and good health supplies aims to maintain the quality of medicines, avoid irresponsible use, maintain the continuity of supplies and facilitate the search and control. The purpose of this study is to see the picture of drug storage and determine indicators of strengths, weaknesses, opportunities and threats that affect drug storage in the warehouse of the pharmaceutical installation of Bolaang Mongondow Selatan Hospital. This research is a qualitative research conducted with a Single Variable Analytical Descriptive Method. The results showed that the picture of drug storage at BolaangMongondow Selatan Hospital has not fully met the requirements according to drug storage standards in the Minister of Health Regulation no. 72 of 2016 with the value per Bolaang Mongondow Selatan Hospital not fully meeting the storage standards according to Permenkes no. 72 of 2016 because it shows a percentage of < 100%. Where the results of the analysis of the suitability of drug storage conditions (73.68%) and fulfillment of drug storage procedures (72.92%) while logistics management is fairly goodwith the percentage of drug suitability between the stock card and the system 100% and the discovery of expired drugs during the 2022 period. The results of the identification of internal factors include advantages, namely a good pharmaceutical supply structuring system, adequate information system facilities, warehouse heads coming from pharmaceutical personnel, good logistics management cycles, the weakness is that there are frequent power outages, warehouse locations that are not separated from pharmaceutical installations, facilities and infrastructure that are still lacking. The opportunities that have are the development of a good Management Information System while threats, distributor regulations, demand for goods or drugs at night, the location of warehouses that are not separated from pharmaceutical installations allow the risk of losing drugs to be even greater.  Keywords: Drug Storage, Pharmacy Warehouse